Efficacy of Antibiotics Against Aeromonas hydrophila and Therapeutic Outcomes in Hybrid Catfish (Clarias macrocephalus × Clarias gariepinus) - Petjul, Keeravit; Panyasai, Chomphunuch; Kan-a-roon, Nattapon; Khunsanit, Prasit; Maichareon, Woraman; Boonmee, Tanaphoom; Kollboon, Urai (Kalasin University Journal of Science Technology and Innovation, 2025)
This study evaluates the efficacy of antibiotics against Aeromonas hydrophila investigates their therapeutic effects on hybrid catfish (Clarias macrocephalus × Clarias gariepinus). The experiment was conducted in two phases. In the first phase, six antibiotics—Penicillin G, Streptomycin, Gentamicin, Erythromycin, Vancomycin, and Ampicillin—were tested for antibacterial activity against A. hydrophila using the agar disc diffusion method. In the second phase, antibiotics that exhibited significant inhibitory effects were selected for in vivo treatment trials in infected catfish. The results demonstrated that Gentamicin, Erythromycin, and Ampicillin showed strong antibacterial activity, with Ampicillin proving most effective in reducing mortality (average 5.33 fish), followed by Gentamicin and Erythromycin (average 6.66 fish). The untreated control group exhibited the highest mortality rate (average 9.66 fish), and the differences among treatments were statistically significant (P ≤ 0.05). These findings indicate that Ampicillin is the most effective antibiotic for controlling A. hydrophila infections in hybrid catfish, highlighting the importance of appropriate antibiotic selection in sustainable aquaculture disease management.